2015
DOI: 10.1037/cfp0000051
|View full text |Cite
|
Sign up to set email alerts
|

Short-term change in couples’ conflict following a transition to parenthood intervention.

Abstract: Conflict among couples was examined following a transition to parenthood intervention to determine both short-term efficacy of the program and elucidate the process of change postintervention. A randomized clinical trial design was used to examine conflict in couples who participated in a transition to parenthood psycho-educational workshop compared with controls. The beginnings of improved communication in conflict were evident at 3 months postbirth through decreased husband contempt and increased husband pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
(62 reference statements)
0
12
0
2
Order By: Relevance
“…(Mitnick et al, 2009). Whilst some TTP relationship interventions have been shown to be effective (Shapiro et al, 2015) and beneficial to parents (Linville et al, 2017), more research is required to improve TTP relationship interventions (Pinquart and Teubert, 2010).…”
Section: Themesmentioning
confidence: 99%
“…(Mitnick et al, 2009). Whilst some TTP relationship interventions have been shown to be effective (Shapiro et al, 2015) and beneficial to parents (Linville et al, 2017), more research is required to improve TTP relationship interventions (Pinquart and Teubert, 2010).…”
Section: Themesmentioning
confidence: 99%
“…Proactive educational programs on this issue might be useful, especially when ties with one or both sets of parents are troubled. Earlier in the couple's development, relationship education programs focused on the transition to parenthood have demonstrated a number of positive outcomes, including lower declines in marital satisfaction (Doss, Cicila, Hsueh, Morrison, & Carhart, ) and improved couple communication during conflict (Shapiro, Gottman, & Fink, ). Likewise, programs centered on building and sustaining mutual support between spouses as roles and responsibilities shift in their relationships with aging parents may buffer the negative impact of stressors related to this transition for the couple's well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…This study has a number of practical implications for future clinical work with middle-aged couples. Research on couple-based interventions thus far has largely focused on how the early years of parenthood affect satisfaction within the marriage (e.g., Feinberg, Jones, Roettger, Solmeyer, & Hostetler, 2014;Shapiro, Gottman, & Fink, 2015). Yet as this and other studies have shown (e.g., Davis et al, 2016;Lee et al, 2016), spouses' experiences in their parental roles remain salient to marital quality across the life course.…”
Section: Practical Implications and Future Directionsmentioning
confidence: 99%
“…Relationship education programs that prepare and guide couples in handling the potential challenges of parenting an adult child may be helpful. Couple-based educational programs focused on the transition to parenthood have demonstrated numerous positive outcomes for families, including better couple communication skills (Shapiro et al, 2015) and long-term gains in children's emotional and behavioral adjustment (Feinberg et al, 2014). Similarly, programs that educate midlife couples on ways to effectively manage relationships with children as their offspring enter young adulthood may be highly beneficial for families.…”
Section: Practical Implications and Future Directionsmentioning
confidence: 99%